Zooming into firms' location, capabilities and innovation performance: Does agglomeration foster incremental or radical innovation? - José-Luis Hervás-Oliver; Francisca Sempere-Ripoll; Carles Boronat Moll (European Research on Management and Business Economics (ERMBE), 2022)
This study answers the question on whether areas of agglomeration or high industry specialization constitute supportive prone-to-innovation environments for the generation of radical innovation. By drawing on the CIS distinction between incremental vs radical innovation, we disentangle the effect of industry specialization on the occurrence of radical innovations, a phenomenon mostly overlooked. By analysing a large dataset of 3,602 firms from CIS and other geographic datasets, results show that a firm's location in high industry specialization areas primarily trims incremental but not radical innovation. Firms' internal knowledge bases do matter more for radical innovation to occur, rather than location in agglomerations. External knowledge available in regions of high industry specialization is redundant for improving a firm's internal knowledge base for radical innovation and it is more likely to merely enable incremental innovation.
Keywords: O33; O31; R58; 650; Industry specialization; Innovation management; Radical innovation